2013
DOI: 10.4028/www.scientific.net/amm.393.487
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Oxygenated Additive on Blended Biodiesel-Diesel Fuel Properties

Abstract: Diesel fuel is widely used in almost all scopes of life, especially in the transportation sector which accounts for 36% of total energy consumed in 2008 in Malaysia. The transportation sector represents the higher energy consuming sector after industrial sector. As the main fuel used in diesel engine now is the fossil fuels which depleting continually accompanied by increasing consumption and prices day by day. Blended biodiesel fuel is considered as alternatives to current fossilized fuels at a low blending l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…These contradictory results indicated that there no one source or method fit all types of biodiesel production, thus, there is a need to conduct more studies to obtain biodiesel by utilize more effective, cost-efficient and friendly-environment method [61].Increasing the efficiency of the fuel utilized in CI engines, which are the most common type of engine, while also reducing their CO2 emissions per kilometer travelled is an attractive goal. Biobutanol, hydrogen, methanol, ethanol and dimethyl-ether are just some of the alternative fuels and energy sources that are now being considered as promising area of investigation [62], [63] [64]. Whilst the highly cost of diesel oil related to the traditional energy use have been well documented, the utilization of biodiesel production from waste cooking oil as a renewable resource is poorly understood [65]- [68].…”
Section: Azil Bahari Alias / Ntu Journal Of Renewable Energy (2023) 5...mentioning
confidence: 99%
“…These contradictory results indicated that there no one source or method fit all types of biodiesel production, thus, there is a need to conduct more studies to obtain biodiesel by utilize more effective, cost-efficient and friendly-environment method [61].Increasing the efficiency of the fuel utilized in CI engines, which are the most common type of engine, while also reducing their CO2 emissions per kilometer travelled is an attractive goal. Biobutanol, hydrogen, methanol, ethanol and dimethyl-ether are just some of the alternative fuels and energy sources that are now being considered as promising area of investigation [62], [63] [64]. Whilst the highly cost of diesel oil related to the traditional energy use have been well documented, the utilization of biodiesel production from waste cooking oil as a renewable resource is poorly understood [65]- [68].…”
Section: Azil Bahari Alias / Ntu Journal Of Renewable Energy (2023) 5...mentioning
confidence: 99%
“…The remarkable issue that my country Iraq encountered in the last few decades is the fragile economic situation and the increase in the prices of fossil oil, which will be vanished one day [13,14]. The biodiesel consists of high energy and carbon-based compound that can be prepared from numerous triglycerides (oil), alcohol, and an acid or base catalyst via a transesterification reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies investigate the eliminate of biodiesel NOx effect by evaluation of formulation strategies [39,40]. This was accomplished by spiking a conventional soy-derived biodiesel fuel with methyl oleate or with cetane improver.…”
Section: Effect Chemical Additives On Engine Performance and Emissionsmentioning
confidence: 99%